Profile of Children Admitted for Severe Acute Malnutrition in a Tertiary Hospital in Southwestern Nigeria - Babatola, Adefunke Olarinre; Olatunya, Oladele Simeon; Ojo, Temitope Olumuyiwa; Taiwo, Adekunle Bamidele; Fadare, Joseph Olusesan (Journal of Nepal Paediatric Society, 2019)
Introduction: This study assessed the socio-demographic profile, outcomes of treatment and challenges encountered in the management of children admitted for Severe Acute Malnutrition at the Paediatric Unit of a State University Teaching Hospital, Ado-Ekiti, Nigeria. Methods: A retrospective cross-sectional study was conducted. The records of twenty-five children with SAM admitted from March 2013-March 2018 were reviewed. SAM was defined according to the Wellcome Classification based on child’s weight and oedema status. Data on demographic characteristics, presenting symptoms, co-morbid conditions, duration of admission and outcome were extracted. Results: There were 13 (52.0%) males and 12 (48.0%) females. The median age of children with SAM was eight months. Eighteen children (72%) were marasmic, four (16%) had kwashiorkor while three (12%) had marasmic-kwashiorkor. Common presenting symptoms included poor weight gain (59.1%), fever (54.5%) and diarrhoea (36.4%). Majority (84.0%) of the patients had co-morbid conditions which included sepsis (66.7%), anaemia (37.5%), hypoglycaemia (16.7%) and hypothermia (16.7%). Twenty-one (84.0%) children were fully vaccinated for age, two (8.0%) had partial vaccination while two (8.0%) were never vaccinated. Only two (8.0%) had exclusive breastfeeding, 19 (76.0%) had mixed feeding from birth. Majority (60%) of the children had one or more social challenges such as teenage parents and financial constraints. Mean duration of admission was 4.56 days. Twelve (48.0%) left against medical advice, nine (36.0%) were discharged, one (4.0%) was referred to another tertiary facility and three (12.0%) deaths were recorded. Conclusions: Many of the children admitted for SAM in our study had social problems and almost half of them left the hospital against medical advice. Besides health problem, social factors may play more role in SAM.